(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2014)
Film narratives are intrinsically time-dependent designs. This article proposes a model of narrative nowness, based on Husserl’s concepts of retention and protention on one hand, and Francisco Varela’s neurophenomenological exploration of time consciousness on the other, relating this further to narrative experience and its neural epiphenomena. Only recently has brain research been equipped with the possibility of dealing with temporal frames relevant for time consciousness in the scope of whole narratives. The study of cinema using neuroscientific methods and insights is referred to as neurocinematics. We promote neurocinematics as a complementary method of traditional film research, rather than an approach of brain sciences in general. Neurocinematic methods may provide film studies with new tools for re-evaluating established filmmaking conventions and developing new ways to study, for instance, the film viewer’s experience and related aspects of time consciousness.